2015
DOI: 10.1063/1.4926809
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional numerical analysis of hybrid heterojunction silicon wafer solar cells with heterojunction rear point contacts

Abstract: This paper presents a three-dimensional numerical analysis of homojunction/heterojunction hybrid silicon wafer solar cells, featuring front-side full-area diffused homojunction contacts and rear-side heterojunction point contacts. Their device performance is compared with conventional full-area heterojunction solar cells as well as conventional diffused solar cells featuring locally diffused rear point contacts, for both front-emitter and rear-emitter configurations. A consistent set of simulation input parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…In SHJ literature, for both experiment [11,21] and simulation [11,15,27], it was found that rear-junction devices benefit from lateral transport in the silicon absorber, while front-junction devices do not. Usually, the contact at the front-side of SHJ front-junction devices is the p-contact.…”
Section: Ii3 Specifics Of Front-vs Rear-junction Shj Devicesmentioning
confidence: 99%
“…In SHJ literature, for both experiment [11,21] and simulation [11,15,27], it was found that rear-junction devices benefit from lateral transport in the silicon absorber, while front-junction devices do not. Usually, the contact at the front-side of SHJ front-junction devices is the p-contact.…”
Section: Ii3 Specifics Of Front-vs Rear-junction Shj Devicesmentioning
confidence: 99%
“…The cells in this study had an emitter on the back side, which was the side opposite to the illuminated side . For the conventional front‐emitter HJ structure, the p ‐layer thickness is determined considering the absorption loss and electrical properties of the p ‐layer.…”
Section: Device Fabricationmentioning
confidence: 99%
“…In this work, we aimed to the efficiency of epi‐Si HJ solar cells by reducing SFs and applying a rear‐emitter structure . We performed spatial current density ( J ) mapping of epi‐Si HJ solar cells by spectral response mapping (SR‐MAP).…”
Section: Introductionmentioning
confidence: 99%
“…The uncontaminated wafers are simulated in Sentaurus Device [17] using the model from [18] with parameters from [19], including the treatment of ITO as a metal. The doping of the/?-a-Si:H layer was increased to 6><10 13 cm" 3 to account for the high pFF in the Suns-Foe measurements.…”
Section: Fitting and Efficiency Potentialmentioning
confidence: 99%